تأثیر تقویت عضلات دور کننده ران و چرخاننده خارج ران بر آسیب اسپرین خارجی غیر برخوردی مچ پا در فوتبالیست‌ها و فوتسالیست‌های مرد: تحقیق تجربی کنترل شده - Amirhossein Roshanfekr; Khalil Khayambashi; Ghasem Yadegarfar; Ahmadreza Movahedi (Vesnu Publications, 2017)
Introduction: Ankle sprain is one of the most common injuries in sport activities. Hip abductor and external rotator weakness may compromise lower extremity alignment and balance, and increase the risk of lateral ankle sprain. The purpose of the present study was to investigate the effect of hip abductor and external rotator strengthening on non-contact lateral ankle sprain in male soccer and futsal players. Materials and Methods: This randomized controlled trial study was conducted on 200 soccer and futsal players which were randomly assigned to two groups. Control group participated in pre-season physical conditioning program which were 1 hour, 4 days a week for 8 weeks. Experimental group participated in the same program for 45 minutes and 15 minutes of selected hip abductor and external rotator strengthening program at each session. Hip abductor and external rotator strength was measured before and after 8 weeks of training. All the players were under surveillance for non-contact lateral ankle sprain during the one season of competition. Results: 8 weeks of selected hip abductor and external rotator strengthening program significantly improved hip strength more in experimental group compared to the control group. In addition, the experimental group significantly experienced less non-contact lateral ankle sprain compared to the control group. Conclusion: Adding isolated strengthening of hip abductor and external rotator to general physical conditioning program decrease the risk of non-contact lateral ankle sprain in male soccer and futsal players.